Moh Sahur Pahang FM Programme reaches out to UMPSA students - Nor Salwana, Mohammad Idris (UMPSA, 2025)
GAMBANG, 14 March 2025 – A total of 400 food packs were distributed, and various food donations were received by students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) in conjunction with the annual Moh Sahur programme, now in its fourth year, organised by Pahang FM in collaboration with sponsors to reach out to those in need.